Framing and reframing the 1992 LA Riots: A study of minority issues framing by the Los Angeles Times and its readers - Oh, Soo-Kwang (2017)
It is common for media messages to show the family since the crisis that this institution is experiencing. It is often conceived not as the place where the person is loved on his own, but as the "power struggles" between his members, especially between woman and man. With the documentary method - bibliographic study - of the conceptual analysis, this paper seeks to clarify some essential elements of the relationships within the family -in order to contribute to a better communication of the family reality- specifically those related to woman and man. From the systemic -non-analytical- methodical proposal of Leonardo Polo, it is proposed that there are three characteristics of this relationship -reciprocity, complementarity, co-responsibility- that have to be studied in their mutual internal connection to understand intrafamily dynamism. In this way it is possible to communicate effectively its reality.